Electrophilic Cyclization of o-Anisole- and o-Thioanisole-Substituted Ynamides: Synthesis of 2-Amidobenzofurans and 2-Amidobenzothiophenes - Kong, Yulong; Yu, Lian; Fu, Lingzi; Cao, Jian; Lai, Guoqiao; Cui, Yuming; Hu, Ziqiang; Wang, Guanhai (Synthesis, 2013)
A facile synthesis of 3-substituted 2-amidobenzofurans and 2-amidobenzothiophenes via electrophilic cyclization reaction of o-anisole- and o-thioanisole-substituted ynamides with I2, NBS and NCS was developed. The products 3-iodo-2-amidobenzofurans were further transferred into 3-aryl-, 3-alkynyl, and 3-vinyl-2-amidobenzofurans via Pd-catalyzed reactions such as Suzuki–Miyaura and Sonogashira cross-coupling reactions and the Heck reaction.
Keywords: 2-amidobenzofurans; 2-amidobenzothiophenes; electrophilic cyclization; ynamide; cross-coupling reaction